METAFORA DALAM NOVEL THE NOTEBOOK KARYA NICHOLAS SPARKS - OLINGER, MATIAS GEORGE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACTS Metaphor is a figurative language that takes two different things by identifying one with another. By using metaphor, it helps the speakers or the writers to give a clear description through comparison. This research aims at finding the metaphor in the novel The Notebook by Nicholas Sparks. The purpose of this research is to get the form of metaphor and the meaning of metaphor through sentences that had been analyzed. The data have been taken from the sentences from all pages of this novel; then they are identified in terms of their forms based on Wahab’s concept and analyzed by based on Bloomfield’s concept about metaphor. The method which is used for this study is descriptive method. In collecting the data, the writer focuses on identifying sentence, phrases, or words. The result shows that the forms of metaphors that the writer found are: Nominative subjective, nominative objective, and predicative metaphors. The result of this study shows that these metaphors contain a certain meaning depending on the sentences where the metaphors are located. ____________________________________________________________________ Key Words : Metaphors, Semantic Analyze, Novel : The Notebook.